A Childhood and Adolescence Policy from a Human Rights Perspective Throughout the Life Cycle - Alpízar Jiménez, Idalia (2024)
This article descriptively outlines the development of the Childhood and Adolescence Policy and the significance of its approval within the context of demographic aging. The expected outcome is that all academic units will recognize the importance of integrated action to have a greater impact on improving the rights of children and adolescents.